The Anatomy of Respiratory Organ of Climbing Perch (Anabas testudineus) - Nuralam, Erica; Luthfi, Muhammad Ja’far (Proceeding International Conference on Science and Engineering, 2019)
The study aims to find out about the anatomical and histological structure of gill organ and labyrinth in Anabas Testudineus. The organ used is gill and labyrinth of climbing perch. The histological observation is done by making the histological preparation applied to a Hematoxylin-Eosin staining. The result of this study shows that the anatomical gill of climbing perch consists of the gill filaments and gill rakers attaching to the gill arch and the cartilage fold which are shaped like a rose. Then, the histological observation of climbing perch gill consists of the gill filament and gill arch. The gill arch is composed of gill rakers, mucosal epithelium, adipose tissue, basal membrane, mucous cell, submucosa, artery, and bone tissue. The gill filament consists of primary and secondary lamella. Primary lamella is composed of cartilage coated by perichondrium, central venous sinus, chloride cell, while secondary lamella is composed of squamous epithelium cell, mucous cell, pillar cell, and erythrocyte. Labyrinth is made up of adipose tissue, elastic cartilage, perichondrium, epithelium, blood vessel, connective tissue, and mucous cell.